Perspectives from health, social care and policy stakeholders on the value of a single self-report outcome measure across long-term conditions: a qualitative study. Issue 5 (19th May 2015) - Hunter, Cheryl; Fitzpatrick, Ray; Jenkinson, Crispin; Darlington, Anne-Sophie Emma; Coulter, Angela; Forder, Julien E; Peters, Michele
Abstract : Objectives: To explore the views of a range of stakeholders regarding whether patient-reported outcome measures (PROMs) can be developed to measure key attributes of long-term conditions (LTCs) care in England, and the potential value of a single generic measure. Design: Qualitative semistructured interview study, analysed using a framework approach. Participants and setting: Interviews with 31 stakeholders from primary care, secondary care, social care, policy and patient-focused voluntary organisations in England. Results: There was broad support for a single PROM that could be used to measure outcomes for patients with any LTCs in any health or social care setting. Interviewees identified three desired uses for a PROM: to improve the quality of individual care; to increase people's engagement in their own care; and to monitor the performance of services. Interviewees felt that a PROM for LTCs should incorporate a mixture of traditional and non-traditional domains, such as functioning, empowerment and social participation, and be codesigned with patients and professional end-users. Stakeholders emphasised the need for a PROM to be feasible for practical implementation at the individual clinical level as a first priority. A number of concerns and potential problems were identified in relation to the application and interpretation of an LTC PROM. Conclusions: This study has demonstrated support for a single self-report outcome measure that reflects the priorities of people with LTCs, if such a measure can be shown to be meaningful and useful at the individual level. People with LTCs and professional end-users in health and social care should be involved in the development and evaluation of such a measure.